2015 4th International Conference on Advanced Computer Science Applications and Technologies (ACSAT) 2015
DOI: 10.1109/acsat.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Modeling User's Trust in M-Commerce Acceptance: A Conceptual Framework in Context of Pakistan

Abstract: with the emergence of internet and World Wide Web, traditional businesses got a new opportunity to compete globally. Traditional bricks-and-mortar businesses became electronic business (e-business) by utilizing Information and Communication Technology (ICT) tools. A new term of Mobile Commerce (M-Commerce) has created tremendous spectrum of business opportunities for businesses. Although there has been large scale adoption of M-Commerce in developingeconomies, but little growth is observed in developing econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It is of interest to note that additional research studies carried out in emerging economies demonstrated the influence of perceived trust in the adoption of m-commerce in Bangladesh and Pakistan (Ding et al, 2019;Rind et al 2015), m-payment services in India (Li ebana-Cabanillas et al, 2020), Smartphone banking applications in Malaysia (Wasiul et al, 2020), e-commerce in Indonesia (Muflih et al, 2020) and Colombia (S anchez-Torres et al 2019). Conversely, research on business initiatives targeting BOP customers has shown that they rarely fit their needs.…”
Section: Perceived Trustmentioning
confidence: 99%
“…It is of interest to note that additional research studies carried out in emerging economies demonstrated the influence of perceived trust in the adoption of m-commerce in Bangladesh and Pakistan (Ding et al, 2019;Rind et al 2015), m-payment services in India (Li ebana-Cabanillas et al, 2020), Smartphone banking applications in Malaysia (Wasiul et al, 2020), e-commerce in Indonesia (Muflih et al, 2020) and Colombia (S anchez-Torres et al 2019). Conversely, research on business initiatives targeting BOP customers has shown that they rarely fit their needs.…”
Section: Perceived Trustmentioning
confidence: 99%
“…Earlier studies have analysed the adoption of MMT services and revealed several factors that impact the acceptance of mobile financial services. Two constructs have also been confirmed as determinants affecting the intention of other mobile financial services, such as mobile banking and mobile payment (Chang, 2014;Khalilzadeh et al, 2017;Le et al, 2020;Rind et al, 2017;Singh and Srivastava, 2018;Tse et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…, 2014). Existing researchers have identified the significance of PC and PS (Pantano and Di Pietro, 2012; Yu, 2012; Rind et al. , 2017; Khalilzadeh et al.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations